О систематическом положении клопа-слепняка Lygus calocoroides Lindh. (Heteroptera, Miridae) - Кержнер, И.М. (Вестник зоологии, 1968)
The species is attributed to the genus Lygocoris. The rediscription of the appearance and figures representing the male genitals are given. Buses is a food plant.